The role of green product as an intermediary of environmental attitude and environmental knowledge on green behavior - Jamal, Fauziyah Nur; Aisa, Nabila Na’ma; Othman, Norfaridatul Akmaliah; Advincula, Geraldine B.; Rohmah, Wafrotur (Universitas Ahmad Dahlan, 2024)
The impact of global warming has made people aware of the importance of environmental preservation. Therefore, it is necessary to implement green product behavior in university environments. However, there is a need for more awareness among students about the use of green products. This research seeks to fill this research gap by developing appropriate green marketing strategies that help implement environmentally friendly behavior in students. This study aimed to determine the mediating role of green products on the influence of environmental knowledge and attitude on the green behavior of students. The sample consisted of 30 respondents, selected using a non-probability sampling technique. The collected data were subsequently processed using Smart PLS. The results show a mediating role of green products on the influence of environmental knowledge and attitude on student green behavior.